Is there constitutional and morphological predisposition to akathisia in schizophrenic patients receiving antipsychotic therapy? - A. A. Goncharova; E. G. Kornetova; A. N. Kornetov; A. V. Semke (Бюллетень сибирской медицины, 2020)
Objective: to identify constitutional and morphological predisposition to akathisia in schizophrenic patients receiving antipsychotic therapy.Materials and methods. 250 patients with schizophrenia receiving basic antipsychotic therapy were studied, aged 40 [32; 50] years old; disease duration was 13 [7; 22] years. The age when the schizophrenic process manifested itself was 23 [19; 30] years. Clinical evaluation of akathisia was performed using the Barnes Akathisia Scale (BARS, BAS), so akathisia was detected in 92 (36.8%) patients. All persons included in the study underwent an anthropometric survey according to the Bunak’s method. Statistical analysis was performed using Statistica for Windows software (V. 12.0), the odds ratio was estimated using the MedCalc® online calculator.Results. The comparative analysis of the Rees – Eysenk body index and Tanner stages in groups of schizophrenic patients receiving antipsychotic therapy with and without akathisia showed no significant differences between them (p = 0.317 and p = 0.347, respectively). Comparison of groups in the distribution of constitutional and morphological types also revealed no statistical differences (p = 0.189). Patients with the andromorphic type of somatic sexual differentiation increased the risk of antipsychotic-induced akathisia (OR = 1.73; 95% CI: 1.02–2.94; p = 0.039) almost twofold.Conclusion. Attribution of patients to different constitutional and morphological types does not play a role in the development of antipsychotic-induced akathisia, unlike attribution to andromorphic somatic sexual differentiation types, which significantly increases its risk.